Physico-Chemical Changes in Muskmelons (Cucumis melo, L.) during Storage - Augustin, M. A.; Osman, Azizah; Azudin, Mohd Nasir; Mohamed, Suhaila (1988)
Fruits of muskmelon (Cucumis melo, L. cv. Asuka) grown under hydrophonic condition were harvested 37 days after anthesis and stored at room temperature (25 - 2lfJC) and at 6 -/Pc. The physicochemical characteristics of the fruits during storage were evaluated. The major limiting deteriorative change during storage at room temperature was softening ofthe fruits. Fruits stored at room temperature had a shelf-life of about 5 days while those stored at 6 - 8 c were acceptable for 3 weeks. The pH and titratable acidity did not change much during storage. There was a slight decrease in total soluble solids and total soluble sugars during storage.